OP31 Towards understanding the 'partner' in partner notification for sexually transmitted infection healthcare: moving beyond the dichotomy of 'regular' and 'casual' partners. (September 2018) - Pothoulaki, M; Vojt, G; Mapp, F; Mercer, CH; Estcourt, CS; Woode-Owusu, M; Cassell, J; Wayal, S; Symonds, M; Nandwani, R; Saunders, J; Flowers, P
Abstract : Background: Partner notification (PN) is a key strategy for sexually transmitted infection (STI) management to reduce transmission and improve population health. It involves contacting sexual partners of people diagnosed with an STI and encouraging testing and treatment to prevent onward transmission, and re-infection. Current UK PN practice tends to conceptualise sexual partner types as 'regular' or 'casual'. However these terms do not sufficiently capture diverse sexual behavioural patterns or STI transmission risk. Given this context, we explored the social relevance, understandings and meanings of contemporary sexual partner types, as a first step in aligning lived realities with clinical practice to improve PN outcomes. Methods: We conducted eleven semi-structured focus groups (November 2016-August 2017), with members of the public (n=38) and sexual health clinic attendees diagnosed with an STI in the past six months (n=19) in England and Scotland. We recruited participants aged 18–65 years who identified as heterosexual or men who have sex with men (MSM), using purposive and convenience sampling. Data were digitally recorded, transcribed and analysed using thematic analysis in NVivo V.10. Results: Findings from the 57 participants (male n=34; female n=23), suggested two key themes in understanding sexual partner types: 1) nature of emotional involvement with the partner(s) and 2) time/continuity of the relationship. Both tapped into participants' relationship perspectives and shaped their understandings and use of partner terms. Interrelated subthemes involved: the different contexts, such as clinical consultations or everyday social interactions, which shaped the use of the terms 'regular' and 'casual' and associated interpretations; and the polysemy and ambiguity of the terms when they were used in combination with other words (e.g. casual sex; casual partner; casual regular) and alternate terms (e.g. random, one-off, serious relationship). There were no differences in the understandings of the terms between heterosexual and MSM participants. Conclusion: This is the first empirical evidence that challenges and provides insight into the dichotomy of sexual partner types in contemporary clinical practice. There is a need for a new socially informed, interdisciplinary classification of sexual partner types to enable better recording and communication between patients, sex partners and healthcare professionals. Improved understanding of partner types will help healthcare professionals develop and tailor PN approaches which address social and cultural influences on the way people form sexual relationships and talk about sex. This will enable targeting of resources to achieve greatest benefit to individual and population health by detecting and preventing STI transmission.